The service system in Al-Mahala Al-Askaria through the manuscript of the era of Aman Beylik Titri (1095 AH). - louaile, Khaled (Journal of Social Sciences and Humanities, 2022)
The manuscript of the era of safety of Mahalat al-Titri (era of Amman Baylk Titri ( is a military document with distinction of the items and légal provisions aimed at achieving discipline within this military unit. It also regulates its relationship with the central and local civil authority represented by Dar al-Sultan and Bayt al-Titri, in addition to determining the internal relations within this unit. This is to draw up the various légal materials that are mentioned in this document and classify them according to basic axes so that the researcher can make use of them and know how to manage the infantry unit known as the military hill, its most important tasks and rules of operation.